2021
DOI: 10.1002/nop2.1022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sandplay therapy in reducing emotional and behavioural problems in school‐age children with chronic diseases: A randomized controlled trial

Abstract: Purpose: Children with chronic diseases exhibit a higher incidence of emotionalbehavioural problems. Though sandplay therapy is a universally recognized psychological treatment method, experimental evidence for this form of therapy is lacking.Our aims were to examine the effectiveness of sandplay therapy in reducing emotional and behavioural problems in school-age children with chronic diseases as well as anxiety and depression in their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Sandplay therapy has the following advantages: ① the games are fun and rich, in line with the psychological characteristics of the age group of the child, who rarely perceives them as therapy and participates in them as a game, ensuring that the therapy is quiet, comfortable, relaxing and enjoyable, and therefore highly acceptable and cooperative [ 18 ]. ② The therapist's company can fully induce the child to create works that vividly reflect the child's inner world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sandplay therapy has the following advantages: ① the games are fun and rich, in line with the psychological characteristics of the age group of the child, who rarely perceives them as therapy and participates in them as a game, ensuring that the therapy is quiet, comfortable, relaxing and enjoyable, and therefore highly acceptable and cooperative [ 18 ]. ② The therapist's company can fully induce the child to create works that vividly reflect the child's inner world.…”
Section: Discussionmentioning
confidence: 99%
“…is suggests that the cartoon text version of the health education booklet combined with sandplay therapy, in addition to medication, can signi cantly improve the psychological status and cognitive function of children with ADHD, as well as improve their intelligence. Sandplay therapy has the following advantages: ① the games are fun and rich, in line with the psychological characteristics of the age group of the child, who rarely perceives them as therapy and participates in them as a game, ensuring that the therapy is quiet, comfortable, relaxing and enjoyable, and therefore highly acceptable and cooperative [18]. ② e therapist's company can fully induce the child to create works that vividly re ect the child's inner world.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at previous studies applying SGT to children, Yeh et al [ 37 ] found that negative emotions in American children who experienced trauma after 9.11 terrorist attacks were alleviated or their intensity decreased after sandplay therapy. Tan et al [ 38 ] observed the effect of sandplay therapy in alleviating anxiety and social problem behaviors in school-aged children with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at previous studies applying SGT to children, Yeh et al [37] found that negative emotions in American children who experienced trauma after 9.11 terrorist attacks were alleviated or their intensity decreased after sandplay therapy. Tan et al [38] observed the effect of sandplay therapy in alleviating anxiety and social problem behaviors in school-aged children with chronic diseases. In a study that affected the reduction of depressive symptoms after SGT intervention, Li et al [39] reported significant decreases in anxiety and depression in children with systemic lupus erythematosus after SGT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that sandplay has a significant therapeutic influence on a variety of mental disorders. Sandplay therapy can reduce anxiety, withdrawal, and social and behavioral issues in school-aged children with chronic conditions, as well as alleviate symptoms of anxiety and melancholy in their caregivers [ 25 ]. One study suggested that sandplay therapy improves ADHD symptoms, such as hyperactivity, impulsivity, and inattention, through symbolic expression, play, and mindfulness [ 26 ].…”
Section: Introductionmentioning
confidence: 99%